A semiquantitative bioassay for relative virulence of Agrobacterium tumefaciens strains on Bryophyllum daigremontiana. - Minnemeyer, S L (1991)
An assay to determine the relative virulence of wild-type and mutant strains of Agrobacterium tumefaciens on leaves of Bryophyllum daigremontiana has been developed. This assay is reproducible, is easy to learn, is not time consuming, and requires little space. The relative virulence of cellulose-minus mutants of A. tumefaciens was investigated with this assay. Some of these mutants were unaltered in virulence, while others showed a marked reduction in virulence.